2010
DOI: 10.1007/bf03347082
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid ultrasound in patients with Turner syndrome: Influence of clinical and auxological parameters

Abstract: Most TS patients presented ATD with a normal thyroid function or subclinical hypothyroidism, without goiter. Dyshomogeneous thyroid structure was also observed in TS patients without ATD. In TS, the evaluation of thyroid volume according to chronological age does not seem to be efficient because of a link between height and thyroid volume. The prevalence of nodular thyroid disease is similar to that observed in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Studies on the frequency of autoimmune thyroid disease have shown increased TPOAb levels in 48.45% of our patients, a finding that is similar to figures reported from Italy ( 32 ) and Denmark ( 33 ), but which is less than in Albania ( 6 ) and Poland ( 35 ). Also, among TS girls with elevated TPOAb levels the number of patients with subclinical and clinical hypothyroidism was greater (77.9%) as compared to other European countries.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Studies on the frequency of autoimmune thyroid disease have shown increased TPOAb levels in 48.45% of our patients, a finding that is similar to figures reported from Italy ( 32 ) and Denmark ( 33 ), but which is less than in Albania ( 6 ) and Poland ( 35 ). Also, among TS girls with elevated TPOAb levels the number of patients with subclinical and clinical hypothyroidism was greater (77.9%) as compared to other European countries.…”
Section: Discussionsupporting
confidence: 90%
“…Hearing defects in patients with TS are characterized by a high frequency of otitis media, assumed to be caused by abnormalities in the eustachian tube and middle ear ( 20 , 28 , 29 ). Patients with TS are reported to have a higher frequency of autoimmune diseases, including autoimmune thyroid disease and celiac disease ( 30 , 31 , 32 , 33 ). Several researchers in Europe have reported increased levels of antithyroid antibodies in patients with TS, the frequency ranging from 36 to 64.8% ( 6 , 30 , 31 , 32 , 33 , 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their measurement is usually recommended at first detection of thyroid dysfunction and/or with thyroid enlargement. The thyroid gland is, on ultrasound, not different from the general population (362). Management of thyroid dysfunction during pregnancy should follow local clinical practice guidelines for any pregnant woman.…”
Section: Autoimmunitymentioning
confidence: 99%
“…Finally, GD in TS patients may often be preceded by HT (about 25.7% of cases), regardless of thyroid function and autoimmunity tests at HT In addition to changes in function, thyroid structural alterations may also be associated with HT [40]. Calcaterra et al found that the prevalence of nodular thyroid disease is similar in TS and in non-TS subjects [38].…”
Section: Turner Syndromementioning
confidence: 99%